Neutralization of local tissue damage induced by Bothrops asper (terciopelo) snake venom - Gutiérrez, José María (1998)
Local tissue damage represents a serious consequence of Bothrops asper envenomations. It encompasses a complex series of alterations, including myonecrosis, dermonecrosis, hemorrhage and edema. Due to its rapid development it is difficult to neutralize by antivenoms, especially if there is a delay in serotherapy. Experimental studies with this venom and the polyvalent (Crotalinae) antivenom produced in Costa Rica indicate that antivenom is effective in neutralizing these toxic activities when incubated with the venom prior to injection. However, if venom and antivenom are injected independently in mice, neutralization of these effects is only partial. Moreover, neutralization is not complete even if homologous or heterologous antibodies are present in the circulation before venom is injected. Despite differences in their pharmacokinetic profiles, equine whole IgG and F(ab')2 antivenoms show similar efficacy in the neutralization of edema, hemorrhage and myonecrosis induced by B. asper venom, suggesting that the use of antivenoms made of antibody fragments may not improve neutralization of these effects. This is due, at least in part, to the fact that microvessel disruption by venom components favors a similar antibody concentration in the affected tissues. Recent advances in the development of neutralizing substances of rapid diffusion, that could be injected locally in the field, may contribute to the neutralization of metalloproteinases and phospholipases A2. In addition, the rapid administration of antivenoms with high antibody titers against locally-acting toxins is very important in the treatment of these effects.